391 Development of the comprehensive score for financial toxicity (COST) tool and assessment of financial toxicity in patients with gynecologic cancer in japan. (18th September 2019) - Kajimoto, Y; Honda, K; Fujiwara, K; Mizuno, M; Nishimura, T; Fujiwara, H; Koyanagi, T; Kohara, I; Tamaki, S; Igarashi, A
Abstract : Objectives: As new medical technology develops, medical costs increase. When high medical costs affect the patient as a toxicity, it is called financial toxicity (FT). In Japan, all patients are covered by the public health insurance system, which may alleviate FT. However, previous research using the Japanese version of the '''''COmprehensive Score for financial Toxicity (COST)''''' tool, whose score quantifies FT, showed that Japanese patients with cancer had FT. Our objective is to analyze its internal validity and the relationship between the COST score and patient information particularly for patients with ovarian, cervical, or endometrial cancer during chemotherapy. Furthermore, this study aims to clarify the correlation between COST and QOL scores. Methods: We will enroll 147 patients, including 49 patients each with ovarian, cervical, and endometrial cancers, from April 2019 to April 2020. Each patient will have been receiving chemotherapy for more than 2 months at enrollment. Each participant will answer the COST tool, EORTC-QLQ-C30, OV28/CX24/EN24, and EQ-5D-5L at baseline and at the end of chemotherapy. The patients will also complete a questionnaire about employment, assets, income, private insurance, medical payments in the last 2 months, presence of children or family members who need a caregiver, and consultation for medical payment before chemotherapy. Results: This research will clarify the characteristics and longitudinal changes in the COST score in gynecologic cancer patients. The impact of FT on the clinical situation will also be determined. Conclusions: We expect to find that the COST score can be used prospectively to improve QOL in patients with gynecologic cancer.